Contested Notions and Practices of Development and Resettlement in Ethiopia: Evidence from Resettlement Sites in Gambella Regional State - Mosisa Gutema, Moti (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2018)
Since 2010, the Ethiopian government launched large scale development plans as part of the Five Year Growth and Transformational Plan. Within this context, the government embarked on resettling pastoral and agro-pastoral communities in the peripheral regions of the country under the broader "vision" of improving the livelihood of the people. The resettlement program was criticized and interpreted differently by actors with competing perspectives and interests for its lack of consent (participation) of the people concerned and for its multidimensional socio-economic and environment consequences. This paper focuses on contested notions and practices of development and resettlement in Ethiopia with particular reference to the implementation of resettlement programs in Gambella. To this end, the study employed triangulation method where multiple sources (Secondary sources and primary sources from government officials, non-government actors, investors and local people) and multiple instruments (interview, personal observation, and focus group discussion) were triangulated. As a method of data analysis, Cernea’s Impoverishment Risks and Reconstruction (IRR) model has been used for analyzing the current and potential risks of the program. The findings of the study revealed that the process of the program implementation was based on pseudo-participation-where the process of implementing the program took the form of informing the people; and pseudovoluntarism principle-where the local community were deceived by unfulfilled promises of government. Finally, based on the data-based model analysis, it has been found out that the resettlement program has resulted in complex sets of consequences that demand policy response from all concerned bodies.